Effect of Inhibiting Upstream Transcription Factor 2 Expression on Proliferation and Apoptosis of Gastric Cancer BGC-823 Cells - WANG Xubin; GAO Shenshuo; ZHANG Zhikai; MA Yan; GUO Xiaobo (Zhongliu Fangzhi Yanjiu, 2022)
Objective To investigate the effect of upstream transcription factor 2 (USF2) on the proliferation and apoptosis of human gastric cancer BGC-823 cells. Methods Lipofectamine?3000 transfection reagent was used to transfect USF2 siRNA into BGC-823 cells (siRNA-USF2 group). Blank control and negative control (siRNA-NC) groups were also prepared. The mRNA and protein expression levels of USF2 in transfected BGC-823 cells were detected by real-time fluorescence quantitative PCR and Western blot, respectively. The proliferation and clone formation abilities of BGC-823 cells in each group were investigated by CCK-8 and plate cloning assay. The apoptosis of gastric cancer cells was examined by flow cytometry. The expression levels of PCNA and apoptosis-related proteins Bax and Bcl-2 in BGC-823 cells were measured by Western blot. Results Compared with those in the blank control and siRNA-NC groups, the mRNA and protein expression levels of USF2 significantly decreased in the siRNA-USF2 group (P < 0.05). At 72 h after transfection, the absorbance in the siRNA-USF2 group was lower than that in the blank control group (P < 0.05). Compared with that in the blank control and siRNA-NC groups, the number of BGC-823 cell clones significantly decreased in the siRNA-USF2 group (P < 0.05). The apoptosis rate of BGC-823 cells significantly differed among the blank control, siRNA-NC, and siRNA-USF2 groups (P < 0.05). Compared with those in the blank control and siRNA-NC groups, the expression of PCNA and Bcl-2 protein decreased and that of Bax protein increased in the siRNA-USF2 group (P < 0.05). Conclusion Inhibiting USF2 expression can suppress the proliferation of human gastric cancer cells and induce their apoptosis. USF2 inhibitors may have important value in the treatment of gastric cancer.